The effects of transcutaneous electric nerve stimulation (TENS) on salivary flow: A study - Dipti Singh; Sudhanshu Agrawal; Mathod C Shashikanth; Neeta Misra (Wolters Kluwer Medknow Publications, 2015)
Aim: This study was undertaken to evaluate the effectiveness of transcutaneous electric nerve stimulation (TENS) as a means of stimulating salivary function in healthy adult subjects. Materials and Methods: Fifty healthy adult subjects with no history of salivary gland disorder were enrolled in the protocol. The TENS electrode pads were placed externally on the skin overlying the parotid glands. Unstimulated saliva was collected for 5 min into graduated tubes. TENS unit was then activated and the stimulated saliva collected for an additional 5 min. Statistical Analysis Used: A paired "t" test was applied to look for statistically significant differences as a group between the amount of unstimulated and TENS-stimulated samples of saliva. Results: Forty-three out of 50 subjects demonstrated increased salivary flow when stimulated via the TENS unit. The mean unstimulated salivary flow rate was 0.354 ml/min (SD 0.19) and the mean stimulated salivary flow rate was 0.49 ml/min (SD 0.24). Statistical analysis of flow rates utilizing the paired t test demonstrated the difference to be statistically significant (P < 0.001). Conclusion: The TENS unit was effective in increasing the salivary flow in two-thirds of healthy adult subjects. A further study in a cohort of patients with salivary gland disorders is warranted.